ANALYSIS OF COST STRUCTURE AND INCOME OF MASK FISH (cyprunus carpio) FISH FISHING IN PADANG GELUGUR KECAMATAN, WEST SUMATERA PASAMAN DISTRICT - Lestari, Fuji (Syarif Hidayatullah State Islamic University Jakarta, 2023)
This study aims to analyze the Cost Structure and Income of Carp Ponds in Padang Gelugur District, Pasaman Regency. The method used in this research is the survey method and direct interviews with carp farmers. Sampling technique using simple random sampling method (randomly) with a sample size of 32 goldfish farmers. The data collected include primary data and secondary data. The data obtained will be processed and analyzed mathematically. The results showed that the cost structure, namely fixed costs of Rp.3,105,438.00 (3.16%), variable costs of Rp.94,899,281 (96.89%), the average fixed costs of Rp.602.29, variable costs on average Rp.18,405, the average total cost of Rp.19,005. Based on the mathematical formula of carp pond business income in Padang Gelugur District averaged Rp20,588,603 / ha / harvest season. Average revenue of Rp118,593,750 / ha / harvest season and the average total cost of Rp98,005,147 / ha / harvest season. Based on the R/C ratio carp farming business is profitable because the R/C ratio of 1.21 > 1. Based on BEP production shows a yield of 4,261 kg, this indicates that carp farmers must achieve production of that size in order to break even. The BEP price of Rp19,007/kg indicates that carp farmers must set a minimum price of Rp19,007/kg in order to reach BEP.